A jó, a rossz és a csúf: Avagy a klasszikus modern, az avantgárd modern és a posztmodern Kosztolányi - Bazsányi, Sándor (Studia Litteraria, 2018)
The essay tries to examine the influence of dezső Kosztolányi with the help of three contemporary poets, György Somlyó, ottó tolnai and Szilárd Borbély. One of them looks at Kosztolányi’s poetry from a classical modern, the other from an avant-garde modern, and the third one from a postmodern point of view.